KEPEMIMPINAN LURAH DALAM MENINGKATKAN PELAYANAN PUBLIK DI KELURAHAN PASIE NAN TIGO - Wais Alqorni (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2019)
This research raises about lurah leadership in improving public services aimed at find out how the leadership of the Lurah in improving public services, the inhibiting factors, and the efforts made by the Lurah in overcoming the inhibiting factors of public services. The research method used is descriptive method with an inductive approach, with data collection techniques by means of interviews, observation, and documentation.The results of this study show that public services have not gone well, because there are still many people who do not know about public services. In his leadership, the Lurah uses several techniques, namely the technique of maturation / preparation of followers, Human Relation Technique, Technique of being an Example, Communication SystemUsage Techniques, the Technique of Providing Facilities. In the implementation there are still found to be inhibiting factors, To overcome these obstacles, the Lurah made several efforts including improving the quality of RT / RW institutions, adding facilities and infrastructure, increasing community participation, and increasing the number of employees. Keywords: Leadership, Public Service